2021
DOI: 10.1002/cm.21693
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of nebulin repeats and evolution of lasp family proteins

Abstract: The LIM and SH3 domain protein (lasp) family, the smallest proteins in the nebulin superfamily, consists of vertebrate lasp‐1 expressed in various non‐muscle tissues, vertebrate lasp‐2 expressed in the brain and cardiac muscle, and invertebrate lasp whose functions have been analyzed in Ascidiacea and Insecta. Gene evolution of the lasp family proteins was investigated by multiple alignments, comparison of gene structure, and synteny analyses in eukaryotes in which mRNA expression was confirmed. All invertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Despite a nuclear export signal, LASP1 is reliant on a nuclear shuttle partner–the tight junction protein zona occludens 2 (ZO2) and potentially AKT1. Phosphorylation of LASP1 at S146 releases the protein from the cytoskeleton (shown for actin and zyxin) and allows the re-localization of the LASP1-ZO2 complex from the outer cell membrane into the nucleus [ 7 ]. In contrast to solid tumors, CML cells show low levels of ZO2 and therefore no nuclear LASP1 localization was detected.…”
Section: Lasp1 and Gene Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a nuclear export signal, LASP1 is reliant on a nuclear shuttle partner–the tight junction protein zona occludens 2 (ZO2) and potentially AKT1. Phosphorylation of LASP1 at S146 releases the protein from the cytoskeleton (shown for actin and zyxin) and allows the re-localization of the LASP1-ZO2 complex from the outer cell membrane into the nucleus [ 7 ]. In contrast to solid tumors, CML cells show low levels of ZO2 and therefore no nuclear LASP1 localization was detected.…”
Section: Lasp1 and Gene Regulationmentioning
confidence: 99%
“…The first nebulin repeat includes a nuclear export signal (NES; aa 71–77) [ 6 ]. A recent molecular evolutionary analysis of vertebrate and invertebrate lasp family proteins revealed that all proteins harbor the same ancestral gene and that the LIM domain, nebulin repeats and SH3 domain are highly conserved between both groups, although the invertebrate lasp linker sequences vary [ 7 ].…”
Section: Introductionmentioning
confidence: 99%